Planetary Spectrum Generator: An accurate online radiative transfer suite for atmospheres, comets, small bodies and exoplanets. (September 2018) - Villanueva, G.L.; Smith, M.D.; Protopapa, S.; Faggi, S.; Mandell, A.M.
Highlights: PSG is a new online radiative-transfer suite (https://psg.gsfc.nasa.gov ) applicable to planets, small bodies and exoplanets for a broad range of wavelengths (0.1 µm–100 mm) from any observatory, any orbiter, or any lander. The radiative-transfer models can ingest billions of spectral signatures for thousands of species from numerous spectroscopic repositories. PSG has a 3D (three-dimensional) orbital calculator for most bodies in the solar system, and all confirmed exoplanets. PSG includes a realistic noise calculator that integrates several telescope/instrument configurations and detector technologies, permitting to model and retrieve planetary signatures. Abstract: We have developed an online radiative-transfer suite (https://psg.gsfc.nasa.gov ) applicable to a broad range of planetary objects (e.g., planets, moons, comets, asteroids, TNOs, KBOs, exoplanets). The Planetary Spectrum Generator (PSG) can synthesize planetary spectra (atmospheres and surfaces) for a broad range of wavelengths (UV/Vis/near-IR/IR/far-IR/THz/sub-mm/Radio) from any observatory (e.g., JWST, ALMA, Keck, SOFIA), any orbiter (e.g., ExoMars, Juno), or any lander (e.g., MSL). This is achieved by combining several state-of-the-art radiative transfer models, spectroscopic databases and planetary databases (i.e., climatological and orbital). PSG has a 3D (three-dimensional) orbital calculator for most bodies in the solar system, and all confirmed exoplanets, while the radiative-transfer models can ingest billions of spectral signatures for hundreds of species from several spectroscopic repositories. It integrates the latest radiative-transfer and scattering methods in order to compute high resolution spectra via line-by-line calculations, and utilizes the efficient correlated-k method at moderate resolutions, while for computing cometary spectra, PSG handles non-LTE and LTE excitation processes. PSG includes a realistic noise calculator that integrates several telescope/instrument configurations (e.g., interferometry, coronagraphs) and detector technologies (e.g., CCD, heterodyne detectors, bolometers). Such an integration of advanced spectroscopic methods into an online tool can greatly serve the planetary community, ultimately enabling the retrieval of planetary parameters from remote sensing data, efficient mission planning strategies, interpretation of current and future planetary data, calibration of spectroscopic data, and development of new instrument/spacecraft concepts.